New Benzodioxole-based Pyrazoline Derivatives: Synthesis and Anticandidal, In silico ADME, Molecular Docking Studies - Özdemir, Ahmet; Sever, Belgin; Altıntop, Mehlika D. (Letters in Drug Design & Discovery, 2019)
Background: Azoles are commonly used in the treatment and prevention of fungal infections. They suppress fungal growth by acting on the heme group of lanosterol 14α-demethylase enzyme (CYP51), thus blocking the biosynthesis of ergosterol. Objectives: Due to the importance of pyrazolines in the field of antifungal drug design, we aimed to design and synthesize new pyrazoline-based anticandidal agents. Methods: New pyrazoline derivatives were synthesized via the reaction of 1-(chloroacetyl)-3-(2- thienyl)-5-(1,3-benzodioxol-5-yl)-2-pyrazoline with aryl thiols. These compounds were evaluated for their in vitro antifungal effects on Candida species. Docking studies were performed to predict the affinity of the most effective anticandidal agents to substrate binding site of CYP51. Furthermore, MTT assay was performed to determine the cytotoxic effects of the compounds on NIH/3T3 mouse embryonic fibroblast cell line. A computational study for the prediction of ADME properties of all compounds was also carried out. Results: Compounds 5, 8, 10 and 12 were found as the most potent anticandidal agents against Candida albicans and Candida glabrata in this series with the same MIC values of ketoconazole and they also exhibited low toxicity against NIH/3T3 cells. Docking results indicated that all these compounds showed good binding affinity into the active site of CYP51. In particular, chloro substituted compounds 8 and 12 bind to CYP51 through direct coordination with the heme group. According to in silico studies, compound 8 only violated one parameter of Lipinski's rule of five, making it a potential orally bioavailable agent. Conclusion: Compound 8 was defined as a promising candidate for further in vitro and in vivo studies.
Keywords: cytotoxicity